The effect of a six months multicomponent training in elderly's body composition and functional fitness - A before-after analysis - Forte, Pedro (2022)
The aim of this study was to assess the elderly’s functional fitness and body composition effects between pre and post multicomponent training program with six months of intervention. The sample of this study was composed of 34 volunteered elders with 68 (± 7.55) years old. The body composition was evaluated by a Tanita BC-545, and a functional fitness test assessed the elderly’s functional fitness. The body composition did not present significant changes between the pre- and post-exercise program intervention. The training program increased the upper limbs’ strength levels and upper body flexibility, and aerobic endurance. Different associations between body composition and functional fitness variables were found between pre and post multicomponent training program. In this study, body composition seems not to be affected. However, functional fitness in upper limbs strength, upper body flexibility, and aerobic endurance improved under six months of multicomponent training.